Different Kinds of Matter(s) – Subjectivity, Body, and Ethics in Barad’s Materialism - Rosfort, René (Kvinder, Køn & Forskning, 2012)
This article questions the methodological conflation at work in Karen Barad’s agential realism. Barad’s immense appeal is first explained against the tense background of the nature/culture antagonism in the twentieth century. Then, by using some of the penetrating observations of a seventeen-century philosopher, Princess Elisabeth of Bohemia, Barad’s “ethico-onto-epistem-ology” is examined and subsequently criticized for disregarding the persistence of subjectivity, dissolving the ambivalence of the bodily matter(s), and neglecting the need for concrete individuality in ethics.